DAMPAK MARKETING MIX “PHYSICAL ENVIRONMENT” TERHADAP KEPUASAAN PASIEN RUMAH SAKIT: LITERATURE REVIEW - Safi’i, Akhmad; Nugroho, Bagus; Kirana, Irin; Muhammadi, Muhammadi; Kamaluddin, Rachmat; Damanik, Regina Destrina; Sulistiadi, Wahyu (UI Scholars Hub, 2021)
Marketing mix strategy is a necessary strategy in service organizations to ensure successful performance. One of the successful performance is measured by patient satisfaction. Patient satisfaction is considered as one of the most important predictors when measuring outcomes and quality of services provided by health facilities. From patient satisfaction obtained loyalty, patient compliance, and has a direct impact on hospital income. This article is built with a literature review obtained from a search database from pubmed and google scholar using the keywords